2018
DOI: 10.3390/pr6040035
|View full text |Cite
|
Sign up to set email alerts
|

Structure Manipulation of Carbon Aerogels by Managing Solution Concentration of Precursor and Its Application for CO2 Capture

Abstract: A series of carbon aerogels were synthesized by polycondensation of resorcinol and formaldehyde, and their structure was adjusted by managing solution concentration of precursors. Carbon aerogels were characterized by X-ray diffraction (XRD), Raman, Fourier transform infrared spectroscopy (FTIR), N 2 adsorption/desorption and scanning electron microscope (SEM) technologies. It was found that the pore structure and morphology of carbon aerogels can be efficiently manipulated by managing solution concentration. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…However, since CO 2 adsorption capacity is a synergistic effect of the pore structure and doped heteroatoms of the material, it is difficult to critically assess the contribution of the combined effects of porosity (pore texture) and chemical composition (heteroatom content and type) to the CO 2 adsorption quantity value, which is because both of them vary with experiment conditions. As reported in the literatures, all the N type in porous carbons exerts a beneficial effect on CO 2 adsorption and CO 2 /N 2 selectivity, but there are no general correlations between the nitrogen content, the type of nitrogen containing-group and the CO 2 uptakes, which also reported by some works. ,, In addition, higher surface area means more pores can be used for gas storage, but there is no clear correlation between the S BET and CO 2 capacities. ,, What’s more, it has been previously reported that the texture property, especially the narrow pore structure, is essential to the CO 2 adsorption capacity. , The effect of the pore volume parameters ( V 0.99 , V DR , V meso , and V <0.8nm ) on the CO 2 adsorption capacities was studied, as shown in Figure b. The results show that there is also no evident dependence between V meso , V 0.99 , and the CO 2 adsorption capacity.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…However, since CO 2 adsorption capacity is a synergistic effect of the pore structure and doped heteroatoms of the material, it is difficult to critically assess the contribution of the combined effects of porosity (pore texture) and chemical composition (heteroatom content and type) to the CO 2 adsorption quantity value, which is because both of them vary with experiment conditions. As reported in the literatures, all the N type in porous carbons exerts a beneficial effect on CO 2 adsorption and CO 2 /N 2 selectivity, but there are no general correlations between the nitrogen content, the type of nitrogen containing-group and the CO 2 uptakes, which also reported by some works. ,, In addition, higher surface area means more pores can be used for gas storage, but there is no clear correlation between the S BET and CO 2 capacities. ,, What’s more, it has been previously reported that the texture property, especially the narrow pore structure, is essential to the CO 2 adsorption capacity. , The effect of the pore volume parameters ( V 0.99 , V DR , V meso , and V <0.8nm ) on the CO 2 adsorption capacities was studied, as shown in Figure b. The results show that there is also no evident dependence between V meso , V 0.99 , and the CO 2 adsorption capacity.…”
Section: Resultsmentioning
confidence: 88%
“…In fact, the results of the correlation between micropore volume at different pore sizes (<0.5, <0.7, <0.8, <1, <2 nm) and the CO 2 adsorption capacities (not shown) clearly indicate that micropores, especially micropores with sizes below 0.8 nm, are the most effective for CO 2 adsorption, with a maximum correlation coefficient R 2 of 0.97. The different values, such as pore sizes less than 0.7 or 1 nm have found to be a critical impact on CO 2 capture capacities. ,, Hence, from these results it can be concluded that although the N and O heteroatoms indeed exist in all the carbon cryogels, the micropore volume, especially micropores with sizes below 0.8 nm appears to be the most important parameter for CO 2 physisorption under 1 bar and 273 K.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…According to our previous work, we have prepared a serious of additional carbon aerogels by regulating the dosage of catalyst and the solution concentration of precursors were used for CO 2 capture. The data selecting and analysis process were elaborated in the supporting information.…”
Section: Resultsmentioning
confidence: 99%
“…Ji et al [11] describe a novel method for determining such pore size distributions based on the measurement of transport parameters and interpreting these through effective medium theory while using a molecular level theory for single pore transport. Qing Liu and coworkers [12] discuss the synthesis of carbon aerogels for CO 2 capture, an application now considered one of the significant challenges of our time. In other adsorption related work, Xue, Ju, and coworkers [13] discuss the synthesis of ion sieves for Li ion adsorption, while Liang, Zou, and Li [14] report the effect of different cyclic stress paths on the damage and permeability changes in gas bearing coal seams.…”
mentioning
confidence: 99%